Melt flow properties of graphite nanoplatelets-filled polypropylene - Bas, Ayse B.; Yilmaz, Oktay; Ibis, Anil; Dogu, Mustafa; Kirkkopru, Kadir; Guner, Fatma S. (SAGE PUBLICATIONS LTD, 2017)
Rheological behavior of polypropylene/graphite nanoplatelet composites of varying content, temperature, and filler shape was investigated by capillary and rotational rheometers. Scanning electron microscope images were taken in order to examine the filler shape and interaction between fillers and polymer matrix. Viscosity measurements of polypropylene/graphite composites showed shear thinning behavior like neat polypropylene. Filler inclusion resulted in increase in shear viscosity and shear thinning behavior of composites. The effect of filler concentration on viscosity is more appreciable in the low shear rate region. PP/graphite nanoplatelet composites with larger interface between filler and polymer matrix were of greater shear viscosity values through the entire shear rate range. However, filler morphology did not affect shear viscosity in high shear rate region remarkably. Composite viscosity as a function of volume fraction was modeled by Maron-Pierce equation. As temperature increased, shear viscosities of polypropylene/graphite composites and neat PP melt decreased. Temperature has less effect on composite viscosity than on neat PP viscosity due to the restricting effect of fillers on polymer molecules.
Keywords: Extrusion; graphite nanoplatelets; melt rheology; composite; polypropylene; HIGH-DENSITY POLYETHYLENE; DYNAMIC RHEOLOGICAL BEHAVIOR; ISOTACTIC POLYPROPYLENE; MECHANICAL-PROPERTIES; EXPANDED GRAPHITE; EXTRUDATE SWELL; CARBON-BLACK; POLYMER NANOCOMPOSITES; THERMAL-CONDUCTIVITY; COMPOSITES; Materials Science